Effectiveness of problem solving skill training with storytelling approach on student s academic self_ disability - Afsane Molaei Moghbeli; Yahya Kazemi; Aboosaied Davarpanah (مطالعات روانشناسی تربیتی, 2023)
The present study was conducted with the aim of the effectiveness of problem-solving skills training with a storytelling approach on students' academic self-handicapping. The method of this research was quasi-experimental with a pretest-posttest design with a control group. The statistical population of the present study included all male students of the sixth grade of primary school in Anbarabad in the academic year 2019-20 (323 people) that one school was selected from among the primary schools for boys by available sampling method. Then, from the sixth grade students who had high scores in academic self-handicapping based on the Jones and Rhodewalt (1982) self-handicapping scale, 40 people were selected and randomly divided into experimental and control groups (20 people in each group). The experimental group received problem-solving skills training with a storytelling approach in 10 sessions of 60 minutes. At the end of the course, the self-handicapping scale was performed for both groups and the results were analyzed using univariate analysis of covariance. The results showed that due to the lower mean scores of the experimental group in the post-test, the value of F obtained is equal to 31.14 which is significant at 99% confidence level (P <0.01). Also, the effect of problem-solving skills training with storytelling approach on students' academic self-handicapping was 45.7% and was significant at the level of P <0.01. Therefore, it can be concluded that to reduce students' academic self-handicapping, problem-solving skills training with a storytelling approach has been effective.